Search for a new pseudoscalar decaying into a pair of muons in events with a top-quark pair at √𝑠 =13 with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Physical review, 2023)
A search for a new pseudoscalar 𝑎-boson produced in events with a top-quark pair, where the 𝑎-boson decays into a pair of muons, is performed using √𝑠 =13 TeV 𝑝⁢𝑝 collision data collected with the ATLAS detector at the LHC, corresponding to an integrated luminosity of 139 fb−1. The search targets the final state where only one top quark decays to an electron or muon, resulting in a signature with three leptons 𝑒⁢𝜇⁢𝜇 and 𝜇⁢𝜇⁢𝜇. No significant excess of events above the Standard Model expectation is observed and upper limits are set on two signal models: 𝑝⁢𝑝 →𝑡⁢¯𝑡⁢𝑎 and 𝑝⁢𝑝 →𝑡⁢¯𝑡 with 𝑡 →𝐻±⁡𝑏, 𝐻± →𝑊±⁢𝑎, where 𝑎 →𝜇⁢𝜇, in the mass ranges 15 GeV<𝑚𝑎<72 GeV and 120 GeV≤𝑚𝐻±≤160 GeV.